Tuberculosis services during the COVID-19 pandemic: A qualitative study on the impact of COVID-19 and practices for continued services delivery in Eswatini - Victor Williams; Alinda G. Vos-Seda; Marianne Calnan; Lindiwe Mdluli-Dlamini; Samson Haumba; Diederick E. Grobbee; Kerstin Klipstein-Grobusch; Kennedy Otwombe (Elsevier, 2023)
Objectives: To describe the impact of the COVID-19 pandemic on tuberculosis services and the different approaches healthcare workers adopted to ensure continued tuberculosis service delivery in Eswatini. Study design: This is a qualitative study with a cross-sectional design. Methods: Thirteen nurses and 9 doctors who provide tuberculosis care from 10 health facilities participated in an in-depth interview to describe how the COVID-19 pandemic affected tuberculosis services and the approaches adopted to ensure continued patient care. Twenty in-person and 2 telephone interviews were conducted. The participating facilities were selected based on a ranking criterion of the number of patients seen. Data were analyzed using thematic content analysis. NVivo 12 software was used for qualitative analysis, and the Consolidated Criteria guided the study for Reporting Qualitative research (COREQ). Results: Two major themes emerged: COVID-19 impacted services delivery and access; and best practices that ensured healthcare services delivery. Six sub-themes describe how COVID-19 impacted services: all attention focused on COVID-19; COVID worsened the health system challenges; COVID hindered patients from accessing care; patients defaulted due to the lockdown; COVID impacted the quality of care and increased the risk of infection among healthcare workers. Five sub-themes describe best practices that ensure continued service delivery: Home-based care, Patient support, Patient Education, Integrated Services, and Staff rotation. Conclusion: While various strategies were adopted globally to mitigate the impact of the COVID-19 pandemic, these strategies need contextualization to be effective and sustainably incorporated into routine care to ensure continuity of and access to TB and other healthcare services.